(untitled) (World Economics and Finance Bulletin, 2025)
Most companies suffer from the challenges of the contemporary business environment, which is characterized by intense competition and high operational costs. This constitutes continuous pressure on the ability of industrial companies to achieve profitability and continuity. In light of these struggles, this research aims to investigate the vital role that value engineering and quality costs can play as strategic management tools for addressing these challenges. To achieve this, the research relies on a descriptive analytical approach, presenting a theoretical framework that demonstrates how these tools can contribute to cost reduction on one hand, and to enhancing competitive advantage on the other. The research concludes that the application of value engineering and quality cost management is no longer a luxury, but has become a strategic necessity for companies wishing to transform their difficulties into a sustainable competitive advantage that ensures their survival and prosperity in the market